2017
DOI: 10.3856/vol45-issue1-fulltext-7
|View full text |Cite
|
Sign up to set email alerts
|

Physical, chemical and zooplankton biomass variability (inshore offshore) of Mexican Central Pacific during El Nino La Nina 2010

Abstract: ABSTRACT. The response of zooplankton, phytoplankton biomass (Chl-a concentration) and nutrients to the oceanographic variability in the Mexican Central Pacific was studied over three oceanographic surveys realized in 2010 (January, May and October). The highest zooplankton biomass (48 mL 1000 m -3 ) was registered in May when nitrites, nitrates, phosphates and silicates were also highest and mean Chl-a was 0.67 mg m -3. The lowest zooplankton biomass was registered in October, with a mean value of 25 mL 1000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
1
10
0
2
Order By: Relevance
“…To explain the first hypothesis, we found that prior to the start of sampling in Cabo Corrientes an intense period of upwelling occurred (April 5-17, Bakun index CUI = 109 m 3 s −1 100 m −1 ), which gradually decreased toward the end of the cruising (April 25, CUI = 40 m 3 s −1 100 m −1 ), when satellite and in situ chlorophyll measurements were the lowest in Acapulco (<1.6 mg m −3 , Supplementary Figure S1). This strong upwelling event, prior to the cruise, may explain the isotherms elevation in the Cabo Corrientes area and the displacement of the warmer water mass off the coast (>25 • C, stations St8 and St9), and the local shoaling of the Subtropical Subsurface Water (StSsW) (Fiedler and Talley, 2006), opposite to the oceanographic conditions occurring in Acapulco, where upwelling was weak at the time of sampling; coastal upwelling events have been previously documented for the coasts of Colima and Michoacán (Davies et al, 2015) and at the entrance of the Gulf of California and Cabo Corrientes (Pelayo-Martínez et al, 2017).…”
Section: Discussionmentioning
confidence: 81%
“…To explain the first hypothesis, we found that prior to the start of sampling in Cabo Corrientes an intense period of upwelling occurred (April 5-17, Bakun index CUI = 109 m 3 s −1 100 m −1 ), which gradually decreased toward the end of the cruising (April 25, CUI = 40 m 3 s −1 100 m −1 ), when satellite and in situ chlorophyll measurements were the lowest in Acapulco (<1.6 mg m −3 , Supplementary Figure S1). This strong upwelling event, prior to the cruise, may explain the isotherms elevation in the Cabo Corrientes area and the displacement of the warmer water mass off the coast (>25 • C, stations St8 and St9), and the local shoaling of the Subtropical Subsurface Water (StSsW) (Fiedler and Talley, 2006), opposite to the oceanographic conditions occurring in Acapulco, where upwelling was weak at the time of sampling; coastal upwelling events have been previously documented for the coasts of Colima and Michoacán (Davies et al, 2015) and at the entrance of the Gulf of California and Cabo Corrientes (Pelayo-Martínez et al, 2017).…”
Section: Discussionmentioning
confidence: 81%
“…of the total population density (Appendix-Figure A1). coastal sectors, allow all organisms to increase their densities more easily [62].…”
Section: Resultsmentioning
confidence: 99%
“…The presence of P. vossi on the southern coast of Jalisco represents a range extension of approximately 600 km from the nearest previous record. This could be explained by the effect of warm water at the time of sampling of the 1997-1998 El Niño event, which could influence the distribution of this species as squids follow their optimum thermal preference (Pecl and Jackson 2008) or because the effect of the local mesoscale structures that transport the organisms from the coast to the open ocean (Godínez et al 2010, Pelayo-Martínez et al 2017. The effect of the same El Niño event was recognized for other loliginid species like Doryteuthis opalescens, which caused this species to move offshore the Southern California Bight (Zeidberg and Hamner 2002).…”
Section: Discussionmentioning
confidence: 99%